Molecular Mechanisms of Poxvirus Evolution - Brennan, Greg; Stoian, Ana M. M.; Yu, Huibin; Rahman, M. Julhasur; Banerjee, Shefali; Stroup, Jeannine N.; Park, Chorong; Tazi, Loubna; Rothenburg, Stefan (mBio, 2023)
Poxviruses are often thought to evolve relatively slowly because they are double-stranded DNA pathogens with proofreading polymerases. However, poxviruses have highly adaptable genomes and can undergo relatively rapid genotypic and phenotypic change, as illustrated by the recent increase in human-to-human transmission of monkeypox virus. Poxviruses are often thought to evolve relatively slowly because they are double-stranded DNA pathogens with proofreading polymerases. However, poxviruses have highly adaptable genomes and can undergo relatively rapid genotypic and phenotypic change, as illustrated by the recent increase in human-to-human transmission of monkeypox virus. Advances in deep sequencing technologies have demonstrated standing nucleotide variation in poxvirus populations, which has been underappreciated. There is also an emerging understanding of the role genomic architectural changes play in shaping poxvirus evolution. These mechanisms include homologous and nonhomologous recombination, gene duplications, gene loss, and the acquisition of new genes through horizontal gene transfer. In this review, we discuss these evolutionary mechanisms and their potential roles for adaption to novel host species and modulating virulence.